Opções de tratamento intravítreo para o edema macular secundário à oclusão venosa de ramo: uma revisão - João Pedro Rodrigues Monteiro (2020)
Branch retinal vein occlusion is a common vascular disorder of the retina and a frequent cause of vision loss. With this study we aimed to review the efficacy and safety of several intravitreal treatment options for macular oedema secondary to this condition. We performed a literature search in the PubMed and Web of Science databases using the terms 'branch retinal vein occlusion' and 'dexamethasone', 'anti-VEGF', 'ranibizumab', 'aflibercept' or 'bevacizumab'. Then, we extracted mean best-corrected visual acuity gains and central retinal thickness values. No formal statistical analysis was performed. Results showed that intravitreal anti-VEGF agents are the safest and most effective treatment, with no significant differences between ranibizumab, aflibercept and bevacizumab. Final visual acuity seemed to stabilize above 70 ETDRS letters. Dexamethasone implants, due to their lower efficacy and adverse effects, should remain a second line choice for this condition.